KELAYAKAN MEDIA KOMIK PADA MATERI JAMUR UNTUK KELAS X SMA - Hidayah, Jujur Ridha; Yeni, Laili Fitri; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to determine the feasibility of comic media as a teaching media on class X high school fungi material. This study consists of two stages, the first stage of comic media creation and second combat media validation. This research is in the form of quantitative and using descriptive method. Comic media validated by 5 validators, 2 Lecturers of Biology Education FKIP Untan and 3 High School Teachers X class, 1 Teacher SMA Negeri 1 Air Besar, 1 Teacher SMA Negeri 1 Kuala Behe and 1 Teacher SMA Negeri 1 Ngabang. The comic media validation instrument uses a validation sheet with 11 criteria. Data analysis using Content Validity Ratio (CVR) and Content Validity Index (CVI). Comic media validation results obtained CVR value of 1.00 on each criterion and overall obtained CVI value of 1.00 and considered as valid or feasible to use as a teaching media of fungi material in class X SMA. Keywords: Comic Media, Feasibility, Fungi Material